Tax-induced earnings management and book-tax conformity: International evidence from unconsolidated accounts - Sebastian Eichfelder; Martin Jacob; Nadine Kalbitz; Kelly Wentland (Arbeitskreis Quantitative Steuerlehre (arqus), 2020)
We quantify the degree of tax-induced earnings management associated with statutory tax rates and examine whether greater book-tax conformity alters this particular type of earnings management. We first validate a new empirical approach for examining tax-induced earnings management using European unconsolidated financial and ownership information over 2005-2013. We provide robust evidence of significant tax-induced earnings management in both domestic and multinational firms. In particular, the results suggest that a 10 percentage point increase in the corporate tax rate relates to an 8.2 percent decrease in pre-tax book income. We then document that firms in countries with greater book-tax conformity engage in additional tax-induced earnings management. This is important given that it contrasts with prior literature, which does not find an effect for book-tax conforming transactions with a change in conformity.
Keywords: H25; H26; M41; 330; tax-induced earnings management; book-tax conformity; conforming tax avoidance